Lindolpho Barbosa Lima e Carlos Chenier : a crítica de arte em Vitória/ES entre as décadas de 1940-1980 - Sales, Sandra Fátima Dias (2011)
The critical one of art in the Espírito Santo not yet possesss characteristics approach that it to the reflections and the aesthetic bases of other Brazilian capitals. The texts on critical of art in the Espírito Santo are characterized by two styles: cro